Muscle activity and activation in previously strain-injured lower limbs: a systematic review - Presland, J. D.; Timmins, R. G.; Maniar, N.; Tofari, P. J.; Kidgell, D. J.; Shield, A. J.; Dickson, J.; Opar, D. A. (Sports Medicine, 2021)
Background: Lower limb muscle strain injury is highly prevalent in running-based sports and is considered a risk factor for recurrent injury. It is possible that differences in muscle activity and activation in previously strain-injured limbs may contribute to the elevated risk of reinjury. Objectives: To systematically review available literature investigating whether muscle activity and/or activation is different in previously strain-injured muscles compared to contralateral uninjured muscles or uninjured controls. Methods: A systematic review of literature in SPORTDiscus, MEDLINE Complete, CINAHL and Web of Science was conducted. Full-text English articles which compared indicators of neuromuscular function between injured and uninjured contralateral limbs or control groups in those with a history of muscle strain injury were included. Results: Twelve studies were included in the review after eligibility criteria were applied. A best evidence synthesis revealed moderate to limited evidence suggesting differences in surface electromyography (sEMG) amplitude, integrated sEMG amplitude, inter-muscle sEMG ratios and voluntary activation in injured limbs, most often during eccentric contractions. Studies utilising sprinting assessments demonstrated conflicting evidence when comparing late swing phase biceps femoris sEMG amplitude between limbs with a history of hamstring strain injury and uninjured contralateral limbs. Conclusions: Differences in muscle activity and activation were observed between injured and uninjured limbs across a variety of strength assessments. The evidence supporting these differences was most often moderate or limited and was generally observed during eccentric contractions. Mostly conflicting or limited evidence was found to suggest that participants with previous hamstring strain injury demonstrate no differences in muscle activity during running tasks when compared with their uninjured counterparts or contralateral limbs.